Predicting ADR from PDR and individual adenoma‐to‐polyp‐detection‐rate ratio for screening and surveillance colonoscopies: A new approach to quality assessment. Issue 5 (1st August 2017) - Schramm, C; Scheller, I; Franklin, J; Demir, M; Kuetting, F; Nierhoff, D; Goeser, T; Toex, U; Steffen, HM
Abstract : Background and aims: Adenoma detection rate (ADR) has been established as a quality indicator for screening colonoscopy. Because ADR is cumbersome to obtain in routine practice, polyp detection rate (PDR), polypectomy rate (PR) and adenoma‐to‐polyp‐detection‐rate‐ratio (APDRR) have been proposed to estimate ADR. This study aimed to evaluate APDRR in order to estimate ADR (ADRest ) in different settings. Methods: Average risk screening and surveillance colonoscopies from a community‐based private practice and a tertiary academic hospital setting were retrospectively evaluated. APDRR was calculated as averaged group APDRR for all study procedures (APDRR) and for the first half of study procedures of each gastroenterologist (APDRRag ) or individually for each gastroenterologist on the basis of his or her first 25, 50 and 100 colonoscopies (APDRRind ). ADRest was determined from PDR by using APDRR, APDRRag, and APDRRind, respectively. Results: A total of 2717 individuals were analyzed. Using APDRR, significant correlations between ADR and ADRest were observed for the entire (0.944, p < 0.001), proximal (0.854, p < 0.001), and distal (0.977, p < 0.001) colon. These correlations were lost when APDRRag was used to estimate each gastroenterologist's ADR for the second half of his or her included colonoscopies. However, ADR and ADRest correlated significantly with a root‐mean‐square‐error of 6.8% and 5.8% when APDRRind on the basis of each gastroenterologist's first 50 and 100 colonoscopies was used for subsequent colonoscopies. Conclusions: ADR for subsequent colonoscopies of an individual endoscopist can be reliably estimated from PDR by using an individually calculated APDRR. Prospective studies are needed to verify this promising approach in different practice settings.